Charlotte's Web - White, E. B. (SCHOLASTIC INC., 1952)
Charlotte's web Wilbur was lovingly raised by a girl bored and lonely - until he meets Charlotte, the beautiful grey spider who also lives in the barn. Charlotte thinks of a wonderful way to save Wilbur from a pig's unhappy fate. Her clever plan will delight you, in this famous story